Analysis of Value-Added Product Mapping From Shellfish Waste in Coastal Areas - Reiga Ritomiea Ariescy; Egan Evanzha Yudha Amriel; Arief Budiman; Laksamana Aditya Hanif Rabbani (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
Coastal areas are one of the areas that currently have many problems, such as environmental problems and community welfare. One of the areas that has problems with these issues is Gisik Cemandi, Sedati, and Sidoarjo. One of the problems in the coastal area is the pile of shells that make the residential environment look dirty, dirty, smelly, and even become a nest for dangerous animals. The purpose of this research is to map the benefits that can be taken from shell waste so that the community can take opportunities of economic value, both as industrial activities, helping to reduce waste, and empowering coastal communities. This research uses a qualitative method with the Snowball Sampling Technique. Based on the results of the study, shell waste can be reduced to several products, namely fertilizer materials, chemical mixtures (calcium carbonate and metal adsorbents), handicrafts, animal feed mixtures, chitin-chitosan, and building material mixtures. Each of these products has its own benefits and selling value. However, this research only focuses on innovation in mapping waste products. This can be a potential opportunity for local communities to provide value to waste and improve welfare.